Potentiality and Attraction of Health Tourism Destination in Thai Regions - Leemingsawat, Wipawadee; Suthitakon, Nopparat; Buddhabhumbhitak, Ketwadee (Academic Journal of Thailand National Sports University, 2018)
This research is aimed 1) to study the potentiality and physical characteristics of health tourism destination and 2) to study the model management and service in health tourism of health tourism destination in Thailand. Samples included 24 personnel, who were responsible for health tourism destination management in 15 provinces in 4 regions of Thailand, from both public and private sectors, and 1,600 foreign tourists who came to visit the health tourism destinations in which the research had been conducted. The researcher had conducted the research in 24 prominent health tourism destinations in Thailand employing mixed method research which included survey research and qualitative research. The data collection tools were observation form, semi-structure interview guide, questionnaire, content analysis, and quantitative analysis which represented frequency, percentage, and mean. The result was found that 3 types of Thailand health tourism destinations which had high potentiality and strong identity are natural health tourism destination, man-made health tourism destination, and integrated health tourism destination. Thailand possessed scenic and abundant health tourism destinations. Some are deemed as World Heritage. Moreover, the combination of natural resources and Thai traditional intellect was applied to create health promoting programs. Most destinations were well managed following required standards. Some were guaranteed by national and international awards. However, sanitation around the destinations needed to be improved. The destinations lacked English speaking personnel and information in English. Besides, public relations communication channels also needed to be increased.